Sexual Violence in Sport: Expanding Awareness and Knowledge for Sports Medicine Providers. Issue 10 (October 2021) - Joy, Elizabeth A.; Herring, Stanley A.; Nelson, Colin; Cohen, Judith; Dugan, Sheila A.; Flatt, Rachael; Goldfarb, Lee; Greinig, Susan; Koontz, Jennifer Scott; Schmitz, Kathryn H.; Wagner, Jessica
Abstract : Sexual violence in sports is underreported and results in a multitude of adverse physical and mental health consequences. Sports medicine physicians, and other members of the athlete care team, should possess knowledge and skill in the prevention of sexual violence and in the care of individuals who experience sexual violence. Abstract: Athletes are vulnerable to sexual violence. Perpetrators of sexual violence may be a trusted coach, a member of the health care team, or a peer. The consequences of sexual violence are wide ranging, resulting in immediate and long-term physical and mental health outcomes that require recognition and comprehensive, multidisciplinary care. Sports medicine providers need to have specific knowledge and skill to care for athletes who experience sexual violence. Several sports organizations ( e.g., International Olympic Committee, United States Olympic and Paralympic Committee, the National Collegiate Athletic Association, and the National Athletic Trainers' Association) have developed policies and procedures to prevent sexual violence and help sports medicine specialists provide care and services for athletes affected by sexual violence. Nevertheless, there remains a need for clinical guidelines, screening tools, and education, as well as clinical best practices to address sexual violence in sports medicine.